ANALISIS POTENSI OBJEK WISATA TAMAN REKREASI MUKOMUKO DI KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Armansyah armansyah; Rahmanelli rahmanelli; Dedi Hermon (JURUSAN GEOGRAFI FIS UNP, 2019)
This study aims to describe the potential data of tourism objects in Muko-Muko Recreational Park in Agam regency, including analysis of potential tourist objects (attraction, accessibility, and infrastructure), visitor perceptions, community participation in economic activities in Muko-Muko Park. This type of research is a quantitative approach research, using primary data and secondary data. Data analysis techniques used are scoring analysis techniques using class intervals and TOWS analysis.